ANTIMICROBIAL POTENTIAL OF LEAVES OF PSIDIUM GUAJAVA - C. J. CHANDEKAR; M. J. MADHUGIRI (The Bioscan, 2011)
The aim of the study was focused on the antibacterial potential of dried leaves solvents extracts of five different extracts (acetone, chloroform, methanol, petroleum ether and water) of Psidium guajava(family Myrtaceae) were tested against Bacillus cereus, Bacillus subtilis,Bacillus megaterium, Staphylococcus aureus, Escherichia coli, Proteus vulgaris and Pseudomonas aeruginosa by well diffusion method.Acetone, methanol and petroleum ether extracts showed significant antibacterial activity.All the organisms are found susceptible except Bacillus cereus. Chloroform extract is active against only Bacillus subtilis. The fresh leaves juice was found to be active against all organisms except Pseudomonas aerugenosa and the aqueous extract found to be active against Proteus vulgaris and Staphylococcus aureus. Results were compared with standard antibiotics Amoxicillin-Am30, Ciprofloxacin-Cf30, Cotrimaxazole-Co25,Gentamicin-G50 and Tetracycline-T30